Peranan Dan Tanggung Jawab Notaris Dalam Memberikan Penyuluhan Hukum Terhadap Para Pihak Di Kota Pekanbaru - Brahma Putra Perkasa (Universitas Islam Sumatera Utara, 2021)
As a general official, a notary is required to be responsible for carrying out his authority so that he can provide legal counseling to the parties before the deed is drawn up. If in the future the deed that has been made turns out to contain a dispute then this definite matter needs to be questioned, whether the error in the deed was caused by the notary, or whether the parties did not provide false information beyond the knowledge of the notary or was there an agreement made between the notary and one of the parties facing, or was it the mistake of the parties who did not provide the documents properly.It is recommended that in the future the notary when conducting legal counseling can be carried out in front of the parties and every legal counseling that has been carried out by a notary and approved by the parties should be written in a deed, or if this cannot be done, the notary can put it in a separate deed, this is done as the evidence that the notary has fulfilled its obligations in providing the legal counseling in connection with the deed to be drawn up.Keywords : Legal Counseling, Responsibilities of a Notary, Law on Notary Position